Dewey Decimal Classification: Edition 19 (1979) to Web Dewey (2018) By M.P. Satija, New Delhi: Ess Ess Publications, 2018. 250 pp. Rs. 1000/-(hardcover) ISBN978-93-87698-28-4 (hardcover) - Husain, Shabahat (Journal of Information and Knowledge, 2021)
The present book titled ‘Dewey Decimal Classification (DDC), Edition 19 (1979) to Web Dewey (2018)’ is the latest addition to Satija’s long list of publications on the subject. Since 1876 when DDC was first published, this system of organizing knowledge is being used in more than 200,000 libraries in 138 countries in more than 30 languages around the globe. The book has come at the juncture when it is needed most by the students and practitioners of classification alike, not only because the subject ‘Library Classification’ is studied globally mainly through various extant systems including DDC but also because the later has completely undergone metamorphosis as to its format, revision policy, and services to the users, especially since 2011, when DDC 23, probably the last in print format, was brought out. The changes that have occurred in the latest version of DDC had commenced from its 19th edition (1979) and have culminated into Web Dewey. The present book under review covers all those changes in addition to its utility as a manual of DDC for practitioners and students alike.